EVALUATE RELATIVE MORTILITY SOME PESTICIDES AND BIOCHEMICALS TO REDUCE THE POPULATION DENSITY OF WHITEFLY Bemisia tabaci (Gennadius) (HOMOPTERA: ALEYRODIDAE) IN BEANS AND CUCUMBER - Mutnai, Hussain Ali (Diyala Agricultural Sciences Journal, 2016)
The experiment conducted durig the season 2013 from April to June in Muradid – Diyala - Iraq, to study the effect of Beauveria. bassiana (BSA3) at concentration of 1 × 10 8 spore / ml , and Licanecillium muscarium at concentration of 1 × 10 7 spore / ml and Spinosad at rate 0.25 ml / l in addition to the tolfenpyrad to reduce the population density of nymphs and adult of whitefly Bemisia tabaci on Beans and cucumbers . The treatment of Mycotal was significantly reduced the population density of whitefly nymphs to 54.49%, followed by Spinosad and the B. bassiana 47.68 % , 42.71 %, respectively. The results showed the effect of tretments in adults of whitefly by Mycotal 52.60%, which the Spinosad 50.615%, and (BSA3) B. bassiana to 38.55%. The conclustion of this study is the use of bio-pesticides on Beans and cucumber can be reduce the population density of whitefly (nymphs and adults) effectively